THE NEW PUBLIC PROCUREMENT LAW (LAW 14.133/2021) AND EXTERNAL CONTROL WITHIN THE SCOPE OF THE TCU: INNOVATIONS, CHALLENGES AND IMPACTS (CIPEEX, 2025)
This study aims to analyze the impacts of Law No. 14.133/2021 on the modernization of public procurement in Brazil, focusing on the oversight role of the Federal Court of Auditors (TCU). The study adopted a deductive method, descriptive research, and a qualitative approach. The research procedure involved a documentary survey for the empirical part, which consisted of a selection of judgments issued between 2021 and 2024. The investigation evaluated the new law's regulatory innovations, such as the National Public Procurement Portal (PNCP), competitive dialogue, and the incorporation of socio-environmental criteria, in addition to identifying the challenges faced in its implementation. The results reveal important regulatory advances, such as the mandatory use of the National Public Procurement Portal (PNCP), the introduction of competitive dialogue, the expansion of contract planning possibilities, the appreciation of sustainability criteria, and the encouragement of transparency and competitiveness. However, the analysis reveals obstacles to the full effectiveness of the new legislation, including: insufficient training of public managers; technological inequality among federal entities; resistance to institutional change; the relaxation of limits on direct contracting, which can weaken oversight mechanisms; and the incipient application of socio-environmental criteria. The conclusion is that Law No. 14.133/2021 constitutes a promising regulatory framework, aligned with contemporary public governance requirements, but its effective implementation requires coordinated efforts in training, investment in digital infrastructure, additional standardization, and strengthening of internal and external oversight mechanisms. The study recommends further empirical research in local contexts and longitudinal monitoring of the law's application, especially in small municipalities.
Keywords: Law.; Public procurement.; Federal Court of Accounts.